Strengthening the Existence of Pesona Bahari Coastal Community Through Lobster Cultivation in the Pandemic Era - Wiga Alif Violando; Moch. Irfan Hadi; Asri Sawiji; M. Chusnan Ma'arif; Nur Maulida Safitri; Puji Maryono; Robayanto Robayanto; Dian Tugu Warsito Taufiq; Abdul Azis; Abdul Muhid (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
The pandemic that ravaged Indonesia caused restrictions on social interaction policy was reduced people's productivity, particularly the micro-economic components and tourism enterprises in coastal areas. An alternative solution was needed to maintain the existence of the coastal community. The participatory research methods were used to find an ideal form of a solution including CBPR and ABCD. The CBPR method was used for community outreach and acculturation. Meanwhile, the ABCD method was used in the process of optimizing community assets. The process of Pesona Bahari community acculturation yields favorable effects in marine cultivation. Asset inventories by the community show that GWD Beach had huge potential to be a lobster farm. Moreover, the community conducts its business process for lobster cultivation operations by involving all internal and external stakeholders. Pesona Bahari community shows a process of enthusiasm and sustained engagement in order to bring social transformation.